ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF IRIS NIGRICANS METHANOLIC EXTRACTS CONTAINING PHENOLIC COMPOUNDS - Sajee' Huwaitat; Ekbal Al-Khateeb; Samira Finjan; Anwar Maraqa (European Scientific Journal, ESJ, 2013)
The presence of natural antioxidant and antimicrobial in plants is well known. This paper reports the antioxidative and antimicrobial activities of methanolic Iris nigricans extracts. Methanolic extracts of Iris nigricans (rhizomes, leaves and flowers) were evaluated for their free radical scavenging activity using the DPPH radical assay. Reduction of DPPH radicals can be observed by the decrease in the absorbance at λ max517nm. The rhizomes extract, leaves extract, flowers extract and ascorbic acid showed antioxidant activity with different IC50 values. The antimicrobial activity of rhizomes extract, leaves extract and flowers extract was done by using disc diffusion method against different species of bacteria and against Candida albicans.